The Conception of Ethical Values in N. Hartmann’s Philosophy - Juršėnas, Nikodemas (Problemos, 1973)
The article discusses the problem of ethical values, their delimitation from other values, and analyses the structure of a moral action. In view of moral alternatives and action, special attention is given to the life situation in which the subject is constantly acting. In analysing the ethical values in N. Hartmann’s philosophy, the author of the article makes an attempt to reveal the specific character of ethical estimations, their dependence upon the life situation.